Efficacy and Safety of Once Weekly Oral Trelagliptin Switched From Once Daily Sitagliptin in the Glycaemic Control of Type 2 Diabetes Mellitus - Nawaz, Muhammad Muzaffar; Iqbal, Muhammad Zafar; Sajid, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder requiring effective long-term glycaemic control. Dipeptidyl peptidase-4 (DPP-4) inhibitors such as sitagliptin are commonly used for glucose regulation. Trelagliptin, a once-weekly oral DPP-4 inhibitor, offers the potential for improved patient compliance. Objective: To evaluate the efficacy (glycaemic control) and safety of once-weekly oral trelagliptin in comparison to once-daily sitagliptin in patients with T2DM. Methods: This quasi-experimental (pre-post intervention) study was conducted at the Diabetes and Endocrine Unit, Nishtar Hospital, Multan, from November 2024 to April 2025. A total of 35 patients aged >12 years with well-controlled HbA1c (6.5–8.5%) on sitagliptin therapy were enrolled. Patients with a history of hypoglycaemia, diabetic ketoacidosis, or diabetic coma in the preceding 6 months were excluded. After switching from sitagliptin to trelagliptin, HbA1c levels were recorded to assess glycaemic control. Data were analysed using SPSS version 26. Quantitative variables were summarized using means and standard deviations, and categorical variables using frequencies and percentages. A paired-samples t-test was used to compare pre- and post-intervention HbA1c values. Results: The mean age of the participants was 49.8 ± 10.5 years, with females comprising 60% of the study population. Mean HbA1c prior to switching (sitagliptin) was 7.37 ± 0.61%, and after switching to trelagliptin was 7.41 ± 0.68% (p > 0.05), indicating comparable glycaemic control. Improved compliance was noted with once-weekly trelagliptin. Minor side effects were reported in 17.1% of patients, with no major or life-threatening adverse events observed. Conclusion: Once-weekly oral trelagliptin demonstrated comparable glycaemic control to daily sitagliptin, with good patient compliance and an acceptable safety profile, making it a viable alternative in the management of T2DM.